1997
DOI: 10.1128/aem.63.1.44-49.1997
|View full text |Cite
|
Sign up to set email alerts
|

Antimycoplasma properties and application in cell culture of surfactin, a lipopeptide antibiotic from Bacillus subtilis

Abstract: Surfactin, a cyclic lipopeptide antibiotic and biosurfactant produced by Bacillus subtilis, is well-known for its interactions with artificial and biomembrane systems (e.g., bacterial protoplasts or enveloped viruses). To assess the applicability of this antiviral and antibacterial drug, we determined the cytotoxicity of surfactin with a 50% cytotoxic concentration of 30 to 64 M for a variety of human and animal cell lines in vitro. Concomitantly, we observed an improvement in proliferation rates and changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(116 citation statements)
references
References 35 publications
(39 reference statements)
1
110
0
5
Order By: Relevance
“…Surfactin is a surfactant structurally related to lichenysin A. It has l-glutamic acid instead of l-glutamine and l-leucine instead of l-isoleucine [23]. We showed that lichenysin A and surfactin both damage the cell membrane and activate the acrosome reaction of boar spermatozoa.…”
Section: Discussionmentioning
confidence: 89%
“…Surfactin is a surfactant structurally related to lichenysin A. It has l-glutamic acid instead of l-glutamine and l-leucine instead of l-isoleucine [23]. We showed that lichenysin A and surfactin both damage the cell membrane and activate the acrosome reaction of boar spermatozoa.…”
Section: Discussionmentioning
confidence: 89%
“…The antiviral activity of LPs was already reported in 1951 by Groupé and colleagues (reviewed in Nybroe & Sørensen, 2004) for viscosin against enveloped viruses. In addition, surfactin was shown to inactivate various enveloped viruses by acting directly on the lipid envelope, leading to disintegration of the virus particles (Vollenbroich et al, 1997b;Huang et al, 2006). Disintegration of membranes was also shown to be the primary activity of surfactin against several human and animal pathogenic mycoplasmas (Vollenbroich et al, 1997a).…”
Section: Role In Antagonismmentioning
confidence: 99%
“…Expression of several operons involved in production of at least four extracellular antimicrobial products is regulated by ComA (Table 1). The antibiotics (TasA, surfactin, sublancin and sporulation killing factor) produced by the products of the tasA, srfA, sunA and skfA (previously ybcO) operons have a variety of activities, including killing other B. subtilis cells (Gonzalez-Pastor et al, 2003), and other bacterial species (Vollenbroich et al, 1997;Kleerebezem et al, 1999;Stover and Driks, 1999;Kearns and Losick, 2003). Additionally, the ComA-regulated yfmH gene product is similar to an antimicrobial cationic peptide (Zuber, 2001).…”
Section: Genes and Processes Affected By The Comx-comp-coma Signallinmentioning
confidence: 99%